Memotivasi Siswa dalam Pembelajaran Pendidikan Agama Krtisten melalui Reward dan Punishment - Semuel Ruben; Samuel Yudistira (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen Duta Harapan, 2022)
Christian Religious Education learning at the State Vocational High School 2 Turen is carried out outside class hours, on Fridays, after study hours. This situation inspires Christian religious teachers to look for ways to increase the motivation of their students to participate in Christian religious learning. One of the methods used is the method of reward and punishment. The researcher aims to determine whether reward and punishment can motivate students to participate in Christian religious education lessons at the State Vocational High School 2 Turen. The type of research used is descriptive qualitative. Therefore, the researcher made conclusions based on the data, information, and facts found through interviews with one teacher and 13 students and supported by existing documents. The results of the study prove that Reward and Punishment is a method that can provide motivation for students who need encouragement in learning Christian Religious Education at State Middle School 2 Turen. AbstrakPembelajarn Pendidikan Agama Kristen di Sekolah Menengah Kejuruan Negeri 2 Turen dilakukan diluar jam pelajaran yaitu pada hari jumat selesai jam belajar. Keadaan ini menggugah guru agama Kristen mencari cara untuk meningkatkan motivasi anak didiknya dalam mengikuti pembelajaran agama Kristen. Salah satu cara yang digunakan adalah metode reward dan punishment. Peneliti bertujuan mau mengethui apakah reward dan punishment dapat memotivasi siswa siswi dalam mengikuti pembelajaran pendidikan agama Kristen di Sekolah Menengah Kejuruan Negri 2 Turen. Jenis penelitian yang digunakan adalah kualitatif deskriptif. Karena itu peneliti membuat kesimpulan-kesimpulan berdasarkan data, imformasi-imformasi, dan fakta-fakta yang ditemukan melalui wawancara 1 guru dan 13 murid dan di dukung dokumen-dokumen yang ada. Hasil penelitian membuktiksn bahwa Reward dan Punisement merupakan suatu metode yang bisa memberikan motivasi bagi siswa siswi yang perluh dorongan dalam belajar Pendidikan Agama Kristen diSekolah Menengah Negri 2 Turen.